2020
DOI: 10.1111/gcb.15142
|View full text |Cite
|
Sign up to set email alerts
|

The stress of Arctic warming on polar bears

Abstract: Arctic ecosystems are changing rapidly in response to climate warming. While Arctic mammals are highly evolved to these extreme environments, particularly with respect to their stress axis, some species may have limited capacity to adapt to this change. We examined changes in key components of the stress axis (cortisol and its carrier protein—corticosteroid binding globulin [CBG]) in polar bears (Ursus maritimus) from western Hudson Bay (N = 300) over a 33 year period (1983–2015) during which time the ice‐free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 104 publications
(153 reference statements)
1
31
0
Order By: Relevance
“…Additionally, Boonstra et al (2020) found a shift in the stress axis of polar bears between 1983-1990 and 1991-2015. In our study, we found a similar temporal pattern in the change in the seroprevalence of T. gondii, F. tularensis and B. bronchiseptica. We do not have direct evidence for the virulence of these pathogens in polar bears, and therefore cannot associate pathogen exposure with survival.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, Boonstra et al (2020) found a shift in the stress axis of polar bears between 1983-1990 and 1991-2015. In our study, we found a similar temporal pattern in the change in the seroprevalence of T. gondii, F. tularensis and B. bronchiseptica. We do not have direct evidence for the virulence of these pathogens in polar bears, and therefore cannot associate pathogen exposure with survival.…”
Section: Discussionmentioning
confidence: 95%
“…These indices subsequently stabilized in the mid‐2000s (Lunn et al, 2016 ). Additionally, Boonstra et al ( 2020 ) found a shift in the stress axis of polar bears between 1983–1990 and 1991–2015. In our study, we found a similar temporal pattern in the change in the seroprevalence of T. gondii , F. tularensis and B. bronchiseptica .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stress also inhibits corticosteroid‐binding globulin production by the liver, further increasing free GC levels. Evidence from several species suggests that milk GC concentrations reflect blood GC concentrations, though they rapidly equilibrate, and so once the stressor ceases and plasma levels decrease, there is a parallel decrease in milk GC levels (modified from Boonstra et al 2020)…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…For example, cortisol and glucose were not influenced by helicopter operations, despite capture stress generally causing their increase (Malisch et al 2018). This may reflect that the hypothalamic‐pituitary‐adrenal stress response is not graded during helicopter captures (i.e., it is more of an off or on response) or that cortisol can be regulated by other mechanisms such as altering concentration of the binding protein (Chow et al 2010, 2011; Boonstra et al 2020). In addition, our assessment of peak values of activity and body temperatures did not consider the effect of different durations between initial captures and recaptures, as 15 of 17 datasets encompassed the same duration (i.e., Aug–Oct).…”
Section: Discussionmentioning
confidence: 99%